IMPLEMENTATION OF RELIGIOUS CHARACTER EDUCATION BASED ON LOCAL WISDOM IN CIVILISATION SCHOOLS IN THE CITY OF CILEGON - Bahyati, Bahyati; Aniyatussaidah, Aniyatussaidah; Inayah, Bidayatul; Hidayah, Ana Nurul; Munji, Ahmad; bin Tamuri, Ab. Halim (Conciencia, 2025)
This study examines the implementation of religious character education based on local wisdom in a civilisation school located in the City of Cilegon. The study is grounded in the premise that the integration of religious values and local cultural practices constitutes a strategic approach to character formation within contemporary educational settings. Employing a qualitative research design with a case study approach, the participants consisted of school principals, Islamic education teachers, classroom teachers, and students selected through purposive sampling. Data were collected through participant observation, in-depth semi-structured interviews, and documentation analysis. The data were analysed using interactive qualitative analysis techniques, encompassing data reduction, data display, and conclusion drawing, with credibility ensured through source triangulation. The findings indicate that religious character values such as honesty, discipline, responsibility, and social care are systematically embedded in school culture through local wisdom practices, including collective Qur’anic recitation, mutual cooperation activities, and the cultivation of interpersonal harmony among school members. Teachers play a central role as moral exemplars and facilitators in integrating religious values into daily routines and culturally grounded educational activities. The study concludes that the implementation of religious character education based on local wisdom contributes significantly to the development of students’ religious attitudes, ethical conduct, and respect for local cultural traditions. This research offers a contextual model that may serve as a reference for other schools seeking to strengthen religious character education through locally grounded cultural frameworks.